Monitoring and auditing mobile operating systems. (2016) - Carabas, Mihai; Carabas, Costin; Gheorghe, Laura; Deaconescu, Razvan; Tapus, Nicolae
The popularity and usage of mobile devices have increased and therefore performance demands changed. An important aspect is represented by the whole system stability which has a big impact on general user experience. This paper proposes a solution for improving the implementation process and stability of operating systems for mobile devices. It presents penetration testing techniques, in order to discover security vulnerabilities. The focus will be on the process of finding the bugs, the exploration part, and the exploitation will only be mentioned to highlight the importance of the vulnerabilities. The second part of the paper consists of a system service which collects the error messages and sends them to a server in order to perform a triage. Received data is saved, processed and then useful information is exposed to developers.